Peluang dan Tantangan Implementasi Kebijakan Pengakuan dan Pembiayaan Pesantren Berbasis Undang-Undang Nomor 18 Tahun 2019 - Imam Djauhari (AHKAM, 2025)
The legalization of recognition and financing of pesantren through Law No. 18 of 2019 has reshaped the configuration of education governance in Indonesia by positioning pesantren within a public funding framework that previously lacked clear operational definition. This study aims to elucidate the institutional opportunities arising from this legal framework while mapping implementation barriers across different levels of bureaucracy. Using an integrated qualitative approach, the analysis combines the review of statutory regulations, ministerial policy documents, and multi-level empirical evidence from the 2019–2024 period, processed through iterative thematic coding to identify regulatory misalignments, capacity gaps, and data system vulnerabilities. The findings indicate significant institutional benefits, including strengthened legal legitimacy for pesantren, expanded channels of state funding, and the emergence of incentives for governance reform. However, several key obstacles are identified, such as disharmony among derivative regulations, uneven administrative readiness across regions, varying consistency in EMIS data, and unequal subnational fiscal commitment. The effectiveness of Law No. 18 of 2019 is shown to depend critically on regulatory harmonization across government tiers, enhanced pesantren management capacity, and the consolidation of standardized, data-driven funding mechanisms. These findings provide a strategic basis for policymakers to integrate pesantren into the architecture of modern public financing without eroding their epistemic and cultural identity as distinctive Islamic educational institutions.